DIETARY ORGANIC MINERAL INFLUENCES THE GROWTH, FEED UTILIZATION AND VERTEBRAL MINERAL CONTENT OF WILD GOLDEN RABBITFISH, Siganus guttatus - Asda Laining; Agus Nawang; Andi Sahrijanna; Muhammad Hafid Masruri; Rachman Syah (Indonesian Aquaculture Journal, 2021)
The positive effect of organic mineral as a dietary mineral source in aquafeed has been recently reported on several species. Nevertheless, the influence of organic minerals on rabbitfish has not yet been determined. The purpose of the present study was to evaluate the effects of different doses of organic mineral on growth and survival, and mineral content in vertebrae of golden rabbitfish, Siganus guttatus. Three diets were formulated containing 0.5%, 1.0%, and 2.0% organic material (OM). A control diet (OM0) did not contain OM. Instead, it was supplemented with an inorganic mineral mixture at a level of 1%. Three hundred fish were randomly selected and distributed in 12 cages to accommodate the four treatments with triplicates. The stocking density was 20 fish per cage. The initial body weight of fish used was 39.2 ± 0.3 g. Fish were fed the test diets twice a day for 150 days. A significant (P<0.05) cubic effect of the treatments was detected on all dependent parameters analysis, excluding feed intake. The influence of dietary OM was not significant for feed intake, indicating that dietary OM did not negatively affect the appetite of rabbitfish. Mineral (Ca, Mg, Zn) content in the vertebrae was significantly improved when dietary OM was included in the diet up to 1% but decreased at the highest inclusion level of 2%. The optimum level of dietary OM to gain the maximum growth rate of rabbitfish was 0.49% as the reflection of the breakpoint of two regressions fitted on specific growth rate (SGR). It is concluded that dietary OM level significantly affected the growth and vertebral mineral content of golden rabbitfish. The study increases our knowledge of the benefit of utilizing dietary OM in the fish diet.